Udaya Parwata's Innovative Music | Musik Inovatif Udaya Parwata - I Wayan Gede Rikiana Adi Putra; Wardizal - (GHURNITA: Jurnal Seni Karawitan, 2024)
This article explains the process of creating music entitled Udaya Parwata to describe the beauty of Mount Agung, which is the highest volcano on the island of Bali. Mount Agung has an essential role in the lives of the surrounding community. The close relationship between Mount Agung and the diversity of Karangasem's traditional arts reflects the harmonious balance between humans and nature. The innovative musical artwork "Udaya Parwata" is based on typical Karangasem arts and instruments combined into one whole. In this work, the stylist wants to highlight the local wisdom of Karangasem with the concept of Mount Agung. The stylist combines Selonding gamelan instruments with Karangasem "important" instruments to create an atmosphere of majesty, holiness, and Mount Agung, which is the source of life, especially for the people of Karangasem.